Implications of Implementing Cooperation with KPBU Scheme at Hang Nadim International Airport-Batam - Zainuddin, Zain; Hasanah, Hani (Lafadz Jaya Publisher, 2025)
Batam's significant economic potential in the Indonesia-Malaysia-Singapore Growth Triangle (IMS-GT), which is attributed to its strategic location near Singapore, high level of security, modern economic sector, advanced infrastructure, and large purchasing power among its population. In this research, the methodology used is autoethnography, with a focus on personal reflection and narrative analysis, with data collected through journals, participant observation and interviews. The Government Cooperation Agreement with Business Entities (GCA), is an alternative collaboration between the Person in Charge of the Cooperation Project (GCA) and the Implementing Business Entity (IBE) which is mutually beneficial for the Parties. Hang Nadim International Airport is the object of PPP cooperation from the Brown Field Project-solicited which was initiated by BP Batam as GCA. The value of the final stage investment project is estimated to be more than IDR 10 trillion. Through an auction process, it was won by a consortium consisting of PT Angkasa Pura 1 with 51% shares, Incheon International Airport (South Korea) with 30% shares, PT WIKA with 19% shares (before dilution). After 3 (three) years of operation, the public using airport services has enjoyed it a lot. The Passenger Terminal Building is better organized, services and facilities at the airport are better with a value (Level Of Service – ref. Minister of Transportation Regulation Number 178 of 2015) of more than 90%. In the near future, Terminal 2 will also be built - with more sophisticated facilities. And besides that, BP Batam as PJPK has obtained concessions each year for a minimum of IDR 50 billion+. In 2025, based on the agreement of the Parties, it will increase to IDR 90 billion+ and share the Revenue of the Cargo Terminal Building. On the other hand, BUP in the first year still suffered losses and in the second and third years it managed to make a profit. Conclusively, the PPP model is suitable for Indonesia, allowing infrastructure development without using APBN funds, improving service quality, and ensuring predictable revenues for the GCA. Apart from the advantages that have been presented, there are obstacles which cannot be addressed in this study. It is hoped that in the coming year there will be significant improvements both in the construction of Terminal 2 and other supporting facilities.